Anarchy, state, and Utopia : Timothy Snyder's interpretive framework for the Holocaust applied to Norway under the Nazi occupation, 1940-45 - Wennström, Johan (IFN working paper, 2017)
Timothy Snyder has suggested an interpretive framework of the Holocaust that runs counter to previous scholarly literature as well as to popular perception. Snyder's central thesis is that the mass murder of Europe's Jewish population should be understood in the context of Nazi policy towards occupied states and the different levels of sovereignty retained by those states. This article applies the criteria of Snyder's concept of "state destruction" on the Nazi occupation of Norway, and finds that Snyder's interpretation of the mechanisms behind the Holocaust derives further support from the Norwegian case. Norway meets eight of the eleven criteria. However, this does not include the complete destruction of its bureaucracy nor the criteria that depend on a state having experienced "double occupation", first by the Soviet Union and then by Nazi Germany. Norway is thus an intermediate case on the spectrum of state destruction and constitutes one of the closest approximations of statelessness in Western Europe during the Holocaust. This finding is a complement both to Snyder's analysis and to the scholarly discussion of its validity.